2018
DOI: 10.1002/mrm.27463
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of time‐dependence for clinically viable diffusion imaging of the spinal cord

Abstract: Time-dependence of clinically viable DW MRI metrics can be detected in vivo in spinal cord WM, thus providing new opportunities for the non-invasive estimation of microstructural properties. The time-dependence of the perpendicular DW signal may feature strong intra-axonal contributions due to large spinal axon caliber. Hence, a popular model known as "stick" (zero-radius cylinder) may be sub-optimal to describe signals from the largest spinal axons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 78 publications
2
32
0
Order By: Relevance
“…(Cheung et al, 2012;Falangola et al, 2008;Henriques, 2018;Lin et al, 2018;Rudrapatna et al, 2014;Sun et al, 2015). Clinical applications of diffusion kurtosis MRI abound, and deeper investigations into kurtosis features, such as time dependence, are being vigorously studied (Grussu et al, 2019;Jespersen, Olesen, Hansen, & Shemesh, 2018;Pyatigorskaya, Le Bihan, Reynaud, & Ciobanu, 2014). Nearly invariably, these measurements are performed using single diffusion encoding pulses sequences; however, these SDE methods cannot separate different sources of kurtosis, which would clearly benefit the field by assigning a degree of specificity to such measurements.…”
Section: Discussionmentioning
confidence: 99%
“…(Cheung et al, 2012;Falangola et al, 2008;Henriques, 2018;Lin et al, 2018;Rudrapatna et al, 2014;Sun et al, 2015). Clinical applications of diffusion kurtosis MRI abound, and deeper investigations into kurtosis features, such as time dependence, are being vigorously studied (Grussu et al, 2019;Jespersen, Olesen, Hansen, & Shemesh, 2018;Pyatigorskaya, Le Bihan, Reynaud, & Ciobanu, 2014). Nearly invariably, these measurements are performed using single diffusion encoding pulses sequences; however, these SDE methods cannot separate different sources of kurtosis, which would clearly benefit the field by assigning a degree of specificity to such measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The model consists of a superposition of a Gaussian component and a series of components exhibiting restricted diffusion in infinite cylindrical geometry. Very recently Grussu et al, demonstrated that modeling the axons as small radii cylinders is a better approximation than the stick model axons. Note, however, that our model neglects any effect of exchange or orientation dispersion.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the relatively good agreement between the SDE and DDE MRI results and the general agreement between MRI and histology, the detailed comparison between MRI and histology in the specific ROIs shows only good to fair agreement depending on the ROI analyzed. This may be the result of several potential impacting factors like the limitations of the modeling of the MRI data which neglect the diffusion time variations and assumes that restriction originates mainly from the intra axonal space although it is clear that it may originate also from the extra axonal space . Additionally, the model does not consider dispersion, which might have some impact even in SC.…”
Section: Discussionmentioning
confidence: 99%
“…Changing the observational time-scale may very well lead to a different set of exponential decays as a result of restricted diffusion 35 and exchange, 36 which implies that the measured DTD may depend on the time-scales or spectral contents of the diffusion-encoding gradients. Even though such time-dependent effects have been measured in human brain white matter, [37][38][39][40][41][42] spinal cord, 43,44 and prostate, 45,46 using stimulated echo or oscillating gradient sequences specifically designed for varying the observational time-scale over extended ranges, the above DTD description holds for the limited range of time-scales probed by clinical dMRI experiments in the brain. 44,[47][48][49][50][51][52][53][54] While (D) provides a simple, and experimentally accessible, description of intravoxel tissue heterogeneity, the inversion of Equation 1constitutes a challenging ill-posed problem, where clearly distinct distributions may result in signal decays that are indistinguishable within the experimental noise, thus complicating the detailed interpretation of dMRI data.…”
mentioning
confidence: 99%